2016
DOI: 10.1159/000441269
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury: Tubular Markers and Risk for Chronic Kidney Disease and End-Stage Kidney Failure

Abstract: Acute kidney injury (AKI) is a common clinical syndrome directly related to patient short-term and long-term morbidity and mortality. Over the last decade, the occurrence rate of AKI has been increasing, and there has also been a growing epidemic of chronic kidney diseases (CKD) and end-stage kidney disease (ESRD) linked to severe and repeated episodes of AKIs. The detection and management of AKI are currently far from satisfactory. A large proportion of AKI patients, especially those with preexisting CKD, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 97 publications
1
23
0
3
Order By: Relevance
“…Furthermore, it was seen that the development of AKI in itself was a significant and independent risk factor for future AKI and this was directly related to the number of AKI episodes. This is possibly because of loss of renal reserve with decline in the number of functional nephrons, maladaptive vascular and tubular repair with each episode of AKI which predisposes these patients to future episodes of AKI . Interestingly, the decline in eGFR in these patients also correlated significantly with the presence and number of AKI episodes again highlighting that each AKI episode may compromise the functional renal mass and therefore the estimated glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, it was seen that the development of AKI in itself was a significant and independent risk factor for future AKI and this was directly related to the number of AKI episodes. This is possibly because of loss of renal reserve with decline in the number of functional nephrons, maladaptive vascular and tubular repair with each episode of AKI which predisposes these patients to future episodes of AKI . Interestingly, the decline in eGFR in these patients also correlated significantly with the presence and number of AKI episodes again highlighting that each AKI episode may compromise the functional renal mass and therefore the estimated glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 93%
“…In recent years, there have been a number of studies about progressive CKD following AKI [30-32]. However, the molecular mechanism of AKI-induced renal fibrosis, which is the main pathological feature of CKD, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent basic science and epidemiologic studies have further suggested a causal role of AKI in the development and progression of chronic kidney disease[15,16]. ZWT is a traditional Chinese medicine whose recipe was recorded in the book “Treatise on Febrile Diseases”, which was written by Zhongjing Zhang during the Ming dynasty, and it has been used for the clinical treatment of kidney impairments.…”
Section: Discussionmentioning
confidence: 99%